Perception of Royal Thai Army Nursing Students towards Elderly Care before Studying Gerontological Nursing - Ankanawin, Usanee; Untaja, Patcharaporn; Yuroong, Arisara; Bohplian, Suweena (Journal of The Royal Thai Army Nurses, 2020)
This qualitative research aimed to study the perceptions of Royal Thai Army nursing students about elderly care without gerontological knowledge. The key informants were 10 nursing students, experiencing on living or taking care of older relatives. The data was collected by in-depth interviews with tape-recorded and transcribed verbatim. The content analysis method was used to analyze these descriptions, including three themes emerged; 1) physical and mental deterioration (physiological change and sickness, be lonely and easily offended), 2) elderly care (helping with daily activities, caring with understanding, caring with attention, adapting to elderly relatives and showing gratitude), 3) roles of elder in their family (looking after grandchildren, assistance in household chores, teaching children and grandchildren), The results of this study provided better understanding of nursing student’s perceptions and attitudes throughout the elderly care from their opinions. In addition, the research distributed useful knowledge to improve the pedagogy of teaching in gerontological nursing for The Royal Thai Army Nursing College. Providing and sharing experiences of elderly care is significantly valuable medical study, especially nursing students not living with their elders to improve caring techniques for elderly patients.